Attitudes of Lithuanian Citizens towards the European Union: Between Enthusiasm and Scepticism - Garškaitė-Antonowicz, Rosita (Politologija, 2025)
This article examines how Lithuanian citizens perceive and evaluate the European Union and Lithuania’s membership in it. While quantitative data from public opinion surveys are overwhelmingly positive, and Eurosceptic political actors are marginal, analysis of qualitative data collected through in-depth and semi-structured interviews reveals a more nuanced picture. Attitudes of a large proportion of informants are multidimensional and ambivalent. The thematic and rhetorical analysis of the interviews with the 80 research participants demonstrates key meanings associated with European integration. Most salient of them are rooted in the existential needs of well-being and security. Criticism towards the EU is based on abstract and concrete political grievances, rejection of the idea of limited sovereignty, feelings of inferiority, and anxiety about value change. The paper also argues that, despite their criticism, informants should not be labelled as Eurosceptics. In the Lithuanian case much more productive strategy is to identify various subcategories of support, ranging from unconditional enthusiasm to cautious ambivalence.
Keywords: European Union; Euroscepticism; interviewing; public opinion